PENGEMBANGAN RUANG KELAS CNC MINI DALAM MENINGKATKAN MINAT BELAJAR TEKNIK PEMESINAN KELAS X - Royani, Fahim; Zuhri, Akhmad Hamdani; Iksannudin, Muhammad; Urroziq , Musyafa’ (LENVARI, 2025)
Current technological developments are rapidly advancing, as seen in the shift towards industrial automation, which is beginning to use robot technology as a substitute for humans. The challenge for vocational high schools is to prepare workers who are ready to face technological developments. The Mini CNC Classroom is an application of this challenge, expected to increase students' interest in learning machining techniques. This development uses the Borg and Gall research method, which involves ten stages of development. Meanwhile, the measurement of learning interest uses a qualitative research method in the form of documents and interviews. The results of the CNC Mini Classroom development can be applied in school environments, particularly at the 10th-grade level. Students' interest in learning is evident through their enthusiasm for learning, and the dropout rate has decreased. Meanwhile, teachers who use the classroom feel supported and are able to develop their teaching effectively.